Does the management of personal integrity information lead to differing participation rates and response patterns in mental health surveys with young adults? A three‐armed methodological experiment. Issue 4 (21st August 2021) - Andersson, Claes; Bendtsen, Marcus; Lindfors, Petra; Molander, Olof; Lindner, Philip; Topooco, Naira; Engström, Karin; Berman, Anne H.
Abstract: Objectives: This study evaluates whether initiation rates, completion rates, response patterns and prevalence of psychiatric conditions differ by level of personal integrity information given to prospective participants in an online mental health self‐report survey. Methods: A three‐arm, parallel‐group, single‐blind experiment was conducted among students from two Swedish universities. Consenting participants following e‐mail invitation answered the World Health Organization (WHO) World Mental Health‐International College Student (WMH‐ICS) mental health self‐report survey, screening for eight psychiatric conditions. Random allocation meant consenting to respond (1) anonymously; (2) confidentially, or (3) confidentially, where the respondent also gave consent for collection of register data. Results: No evidence was found for overall between‐group differences with respect to (1) pressing a hyperlink to the survey in the invitation email; and (2) abandoning the questionnaire before completion. However, participation consent and self‐reported depression were in the direction of higher levels for the anonymous group compared to the two confidential groups. Conclusions: Consent to participate is marginally affected by different levels of personal integrity information. Current standard participant information procedures may not engage participants to read the information thoroughly, and online self‐report mental health surveys may reduce stigma and thus be less subject to social desirability bias.